Data resource profile: Cardiovascular H3Africa Innovation Resource (CHAIR) (2018)
Low- and middle-income countries (LMIC) constitute the majority of the world’s population and bear more than 80% of the global burden of cardiovascular disease (CVD).1,2 The recent increases in CVD globally are also reflected in LMIC, where the prevalence of overall deaths from CVD was 28% in 20013 and premature CVD mortality was 37% in 2015.4 The paucity of data regarding the drivers of the CVD epidemic and contextualized solutions is, in part, because less than 10% of the global research resources and facilities for implementation are found in LMIC.5,6 Therefore LMIC are particularly disadvantaged in dealing with the CVD burden with...